2015
DOI: 10.1039/c5cp03975d
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of electroactive β phase crystallization and dielectric constant of PVDF by incorporating GeO2 and SiO2 nanoparticles

Abstract: Poly(vinylidene fluoride) (PVDF) nanocomposites are recently gaining importance due to their unique dielectric and electroactive responses. In this study, GeO2 nanoparticles/PVDF and SiO2 nanoparticles/PVDF nanocomposite films were prepared by a simple solution casting technique. The surface morphology and structural properties of the as-prepared films were studied by X-ray diffraction, scanning electron microscopy, and FT-IR spectroscopy techniques. The studies reveal that the incorporation of GeO2 or SiO2 na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 55 publications
2
68
0
Order By: Relevance
“…A 15 wt% SiO 2 -loaded PVDF lm exhibited a high permittivity, due to the homogeneous dispersion and interfacial interaction of SiO 2 nanoparticles in the PVDF matrix. 131 For a P(VDF-co-HFP) matrix lled with mesoporous SiO 2 nanorods, the anisotropic shape of the SiO 2 nanorods and ordered mesopores doubled the amount of the -OH groups present. This increased the intermolecular interactions and enhanced the bphase content and ferroelectric properties of P(VDF-co-HFP).…”
Section: Structure Of Polyvinylidene Uoride (Pvdf) and Polymorphsmentioning
confidence: 99%
“…A 15 wt% SiO 2 -loaded PVDF lm exhibited a high permittivity, due to the homogeneous dispersion and interfacial interaction of SiO 2 nanoparticles in the PVDF matrix. 131 For a P(VDF-co-HFP) matrix lled with mesoporous SiO 2 nanorods, the anisotropic shape of the SiO 2 nanorods and ordered mesopores doubled the amount of the -OH groups present. This increased the intermolecular interactions and enhanced the bphase content and ferroelectric properties of P(VDF-co-HFP).…”
Section: Structure Of Polyvinylidene Uoride (Pvdf) and Polymorphsmentioning
confidence: 99%
“…However, the value of the dielectric constant is low as compared to that of the PVDF-KNN nanocrystal composites. The increase in dielectric constant in the nanocrystal composites is chiefly attributed to an increase in dipole-dipole interaction between the PVDF polymer and the KNN nanocrystals at the interface and also due to ion-dipole interaction between the surface of the nanocrystallites and the PVDF matrix [18,[54][55][56][57][58].…”
Section: Dielectric Propertiesmentioning
confidence: 99%
“…The infrared spectrum of the PVDF films prepared in presence of CuONPs is shown in Figure 3b). Apparently, the presence of CuONPs did not dramatically affect the intensity and wavenumber It is reported that the addition of metal oxide nanoparticles to the PVDF casting solution causes the -to -phase conversion [13,22]. As can be noted, the F() values are similar within the studied CuONPs composition range (2-10 wt.…”
Section: Atr-ft-ir and Raman Cuo@pvdf Characterizationmentioning
confidence: 64%
“…The infrared spectrum of PVDF mainly covers the low wavenumber region (Figure 3b). The -CF2 wagging (489 cm -1 ) and bending (610 cm -1 ), the skeletal bending (764 cm -1 ), the -CH2 rocking (795 cm -1 ) and twisting (975 cm -1 ) are some of the peaks characteristic of the non-polar -phase of PVDF (indicated by black arrows, Figure 3a) [13,21,22]. Two peaks, labeled with black arrows in Figure 3a (at 510 cm -1 and 840 cm -1 corresponding to the -CF2 stretching -CH2 rocking, respectively)…”
Section: Atr-ft-ir and Raman Cuo@pvdf Characterizationmentioning
confidence: 99%
See 1 more Smart Citation